Analisis Nilai Pendidikan Kewirausahaan Siswa pada Mata Pelajaran Mulok Green Lab SDIT Alam Cahaya Toboali - Liana Andini; Diana Pramesti; Sasih Karnita Arafatun (STKIP Andi Matappa Pangkep, 2023)
The purpose of this study is to describe the values of student entrepreneurship education in the green lab local content subject at SDIT Alam Cahaya Toboali. This type of research is qualitative research using descriptive research types. In collecting data using observation and interview methods. The data collected is in the form of words which are analyzed through data collection, data reduction, data presentation, and verification. Then to check the validity of the data with triangulation. The results of research conducted at SDIT Alam Cahaya Toboali show that indicators of the values of student entrepreneurship education in green lab local content subjects have not been well achieved. Based on the results of the analysis obtained through interviews, it was stated that the values of Entrepreneurship Education obtained by students in green lab learning activities at SD IT Alam Cahaya Toboali from the 6 students interviewed the most dominant emerged, namely independent values seen when students prepared their own green lab gardening equipment; creative value is seen when students are able to utilize used goods to be used as polybags for plant seeds; and action-oriented values that are seen when students are happy to apply their ideas in green lab learning.